131 NO PATHOGENIC MUTATIONS IDENTIFIED IN THE COL8A2 GENE OR FOUR POSITIONAL CANDIDATE GENES IN PATIENTS WITH POSTERIOR POLYMORPHOUS CORNEAL DYSTROPHY. (1st January 2005) - Sampat, K. M.; Aldave, A. J.; Rayner, S. A.; Yellore, V. S.; Principe, A. H.; Momi, R.; Raber, I.; Hannush, S. B.; Stulting, D.
Abstract : Purpose: To identify the genetic basis of posterior polymorphous corneal dystrophy (PPCD) through the screening of the COL8A2 gene. Mutations have previously been identified in COL8A2 in affected patients and in four other positional candidate genes. Methods: We performed DNA extraction, PCR amplification, and direct sequencing of the COL8A2, BFSP1, CST3, MMP9 and SLPI genes in 15 unrelated, affected patients as well as in unaffected family members. Results: In the COL8A2 gene, none of the four previously identified presumed pathogenic variants were identified in affected patients. However, a missense mutation previously identified in normal controls, Thr(502)Met, was identified in 2 of the 15 affected probands. In addition, several novel and previously identified single nucleotide polymorphisms were found in the COL8A2 gene and the other positional candidate genes. These single nucleotide polymorphisms resulted in various synonymous and missense amino acid substitutions but no presumed pathogenic sequence variants were identified in the COL8A2, BFSP1, CST3, MMP9 or SLPI genes. Conclusions: No pathogenic mutations were identified in the COL8A2 gene or the four positional candidate genes in a series of patients with PPCD. The implication of this implies that other genetic factors are involved in this autosomal dominant dystrophy.